Midea Group Co. Ltd / Siti Saihah Ibrahim - Ibrahim, Siti Saihah (2022)
What is rice cooker? A commercial Rice Cooker is a compact countertop appliance designed to cook large quantities of rice with the minimum amount of supervision. Consisting of a non-stick inner bowl, thermostat control and heating element, the rice cooker is incredibly simple to use, yet a massively valuable asset for businesses which require bulk quantities of rice on a daily basis. The first rice cooker was introduced in Japan by Toshiba in 1955. Due to its huge popularity, other companies soon joined the market, adding innovations that expanded the abilities and features available. Cooking rice had traditionally been a process which required the utmost attention to ensure the rice was cooking properly. Electric rice cookers automate the process by mechanically or electronically controlling heat and timing, thus freeing up a space on the hob and the attention normally reserved for rice cooking. Although rice cookers do not necessarily speed up the cooking process, with an electric rice cooker the cook's involvement in cooking rice is reduced to simply measuring the rice, preparing the rice properly and using the correct amount of water - the rest of the process is automated. Many modern cookers have heat insulating casing and a warming mechanism. When the rice is determined to be fully cooked, the unit will automatically switch to the "keep warm" cycle, which prevents the rice from being overcooked and keeping the rice warm until it is ready to be served. It takes around 30 minutes to one hour for most electric rice cookers to complete cooking. The time required mainly depends on amount of rice used, as well as the power of the heating elements. By using an electric pot requires electrical conduction and cannot be used if electricity is turned off or place where there is no source of electricity. So, a rice cooker using pressure is the solution to this problem. A pressure cooker looks like a regular pot but has a modified lid that locks on over a rubber gasket to create a seal. The cooker works by raising the temperature of boiling water, thereby speeding up the time it takes to boil, braise, or steam. A pressure cooker cooks food about 30 percent faster than conventional methods like steaming, boiling, and braising. According to the American Council for an Energy-Efficient Economy, pressure cookers also use 50 to 75 percent less energy due to shorter cooking times. Pressure-cooked foods retain more vitamins and minerals (as well as flavor) than boiled foods because there is less water into which nutrients can dissolve. It is not only a large pot but also easy to operate with a very simple button function. This pot with a cooking indicator light and heater function makes it easy for you to know whether the rice is being cooked, ready to eat or being reheated.